An experimental investigation of the fracturing behaviour of rock-like materials containing two V-shaped parallelogram flaws - Jinjin Tian; Dongjing Xu; Tianhao Liu (International Journal of Mining Science and Technology, 2020)
The distribution characteristics and evolution law of rock mass fissures induced by mining are a key scientific issue in the study of deep rock mechanics. In this study, a series of uniaxial compression experiments was conducted on rock-like specimens containing double V-shaped prefabricated fissures at dip angles of α = β = 45°, α = 45°<β = 60°, α = β = 60°, and α = 60°<β = 75° with a rock mechanics servo-controlled testing system. According to the experimental results, the effects of the dip angles of the double V-shaped prefabricated flaws with the same area on the mechanical parameters and fracturing process of the specimens were analysed in detail. Additionally, the crack initiation stress presented a nearly linear growth trend, which is generally similar to that of the crack peak stress with increasing flaw dip angle. By applying photographic monitoring to the crack initiation, propagation, coalescence, and failure modes in rock-like specimens, it was easily seen that the V-shaped flaw properties slightly influence the crack initiation positions but significantly influence the crack trajectories. The crack failure modes can be summarized into two distinct types. The study reported herein can provide a better understanding of the evolution of double V-shaped prefabricated fissures induced by coal mining.